2009
DOI: 10.1088/1367-2630/11/12/123027
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of a maximally entangled state by repeated on- and off-resonant scattering of ancilla qubits

Abstract: A scheme for preparing two fixed non-interacting qubits in a maximally entangled state is presented. By repeating on-and off-resonant scattering of ancilla qubits, the state of the target qubits is driven from an arbitrary initial state into the singlet state with probability 1 (perfect efficiency). Neither the preparation nor the post-selection of the ancilla spin state is required. The convergence from an arbitrary input state to the unique fixed point (mixing property) is proved rigorously, and its robustne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 33 publications
(52 reference statements)
1
37
0
Order By: Relevance
“…It should be remarked, though, that the level of control required by the present proposal is extremely low. Furthermore, the latest findings on setups analogous to those addressed here [18] have shown that a suitable modification of the schemes in Refs. [16,17] can allow for deterministic singlet-state preparation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It should be remarked, though, that the level of control required by the present proposal is extremely low. Furthermore, the latest findings on setups analogous to those addressed here [18] have shown that a suitable modification of the schemes in Refs. [16,17] can allow for deterministic singlet-state preparation.…”
Section: Discussionmentioning
confidence: 78%
“…Very recently, it has been demonstrated [16,17] that efficient entanglement generation can be achieved even by fully relaxing any preparation and postselection of the mediators' internal quantum state: Mere injection of a manifold of unpolarized mobile particles that have trespassed the scattering region, as recorded by a Geiger-like detector [19], can suffice to distribute maximum entanglement [16,17]. The latest achievements have shown that such a strategy can be modified so as to deterministically establish maximum entanglement [18].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it has been shown [27] that in the case of two spin-1/2 centers the singlet-extraction protocol that we have used here can be modified so as to make it deterministic. Extension of this procedure to the various situations addressed in this paper is under current investigation.…”
mentioning
confidence: 99%
“…The first demonstration was in application to quantum phase estimation [1][2][3][4][5]. Another application of the adaptive measurement is for state preparation [6][7][8][9][10]. A striking feature of this scheme is that the desired time evolution of the state is brought about only by the measurement backaction, and there is no need to introduce any external force for controlling the state.…”
Section: Introductionmentioning
confidence: 99%